Dielectric Properties of Filled Composites of Epoxy Resin - Fareeda Farrukh,; Shahid H. Zaidi, (Journal of Basic & Applied Sciences, 2014)
The addition of fillers in composite of epoxies, improves the dielectric response of the epoxies. The dielectric properties of unfilled and filled composites of epoxy resins have been studied as a function of thickness in the frequency range 10-1 Hz to 105 Hz at room temperature. The response of the unfilled samples shows that the composites behave as an insulator for all thickness. In filled composites at small thickness (0.32 mm) the response shows a loss peak in low frequency regime. The peak is broader than the Debye loss peak which is obscured by the dc conductance. At frequencies greater than p the response shows a well defined power law behaviour after the subtraction of C. Similar behaviour has been observed at different thickness.